Causation without a cause. (2nd November 2015) - Cuervo, María Cristina
Abstract: This article develops a constructionalist approach to "lexical" causatives, as in The sun melted the snow . It is argued that causation is a truly configurational meaning, arising as the interpretation of the syntactic combination of two verbal heads, the higher v representing the causing event (an unspecified dynamic vdo ) and the lower v representing the resulting state named by the verbal root (a stative vbe ). This structure contrasts with that of simple transitive activity verbs, which are monoeventive (vdo ). A parallel contrast is established between bieventive inchoatives (vgo –vbe ), as in The snow melted, and simple unaccusatives, as in The guests arrived (vgo ). In this analysis, causatives and inchoatives both comprise two events and have an intersective nonderivational relationship. They share the lower resulting state; the type of the higher event distinguishes between the two. The analysis—developed with attention to Spanish data—can straightforwardly account for observed gaps in the causative alternation, the distribution of bare nouns, and scope ambiguity of adverbials and negation, and it sheds new light on the presence of reflexive morphology in inchoatives. The analysis implies that transitivity, as well as unaccusativity, can arise from two basic syntactic structures, on which distinctive verbal meanings are built. In this theory, no syntactic terminal or lexical verb expresses a relation between events; relations between events—such as causation, change of state, and resultatives—arise via semantic composition rules that interpret complex syntactic structures.